Weekly Physiological Changes in Blood Pressure During Three Weeks Daily Consumption of 10 Grams of Cocoa Powder Among Young Black Africans in Côte d’Ivoire - Siransy-Balayssac, Edwige; Ouattara, Soualiho; Ahiboh, Hugues; Youzan, Toh Bi; Gouh, Fagnan Levy; Yao, Koffi Bertrand; Ehouman, Mocket; Dah, Cyrille Serges; Bogui, Pascal (Frontiers in Physiology, 2021)
Background: In Caucasians, regular consumption of cocoa induces a drop in arterial blood pressure via an increase in nitric oxide production. However, black individuals have a different nitric oxide biodisponibility compared to Caucasians. The aim of this study was to determine, in black Africans, the physiological variations in arterial blood pressure among cocoa consumers. Method: In total, 49 male black African volunteers, aged between 18 and 30 years old, were randomized into two groups; those consuming 10g of cocoa powder per day (1680 mg of flavonoids per day) for 3 weeks (consumer group), and those not consuming cocoa (control group). Systolic (SBP) and diastolic blood pressures (DBP), and heart rate (HR) were measured in the morning on an empty stomach (fasting), on day (D) 1 (without cocoa), D8, D15 and D22. Data were collected by groups and by subgroups established according to the level of SBP, DBP or HR on D1. The means and variations of the means (between D1 and the subsequent days) of the recorded parameters were calculated and compared between groups and between subgroups. Results: On D8, the variations in SBP in the consumer group were significantly different from the control group (-3.72 ± 6.01 versus 0.57 ± 6.66 mmHg; p = 0.02). Between the control and consumer subgroups according to SBP, no statistical difference in the means or variations in SBP was noted. On D8 and D22, the variations in the SBP of consumers with SBP ≥110 mmHg on D1 were significantly different from those of other consumers (D8: -6.55 ± 5.96 versus -1.1 ± 4.93 mmHg; p = 0.01; D22: -6.63 ± 7.77 versus 0.35 ± 5.58 mmHg; p = 0.01). In the subgroups with a DBP <75 mmHg on D1, the mean DBP of the consumers was significantly lower than that of the controls on D8 (65 ± 5 versus 69 ± 6 mmHg; p = 0.03). Conclusion: In young black African men living in Côte d’Ivoire, regular consumption of cocoa resulted in a decrease in SBP and DBP. The decrease in SBP appeared to be greater the higher the baseline SBP was